Statistical CUSUM designs with minimum sampling cost. Issue 4 (4th July 2018) - Saniga, Erwin M.; Davis, Darwin; McWilliams, Thomas; Lucas, James
ABSTRACT: We develop a method of designing CUSUM control charts that yields minimum sampling costs while meeting statistical constraints on the average time to signal when there is no assignable cause and the average time to signal when there is an assignable cause. We call this method statistical CUSUM design with minimum sampling costs. Numerical examples are given which show the dominance of this method over the usual statistical design method with the only disadvantage being the small additional effort to estimate sampling costs. The designs we compute are compared to recommended CUSUM statistical designs as well as economic statistical designs.